Leadership Quality on Service through Career Development and Public Service Motivation - kurniawaty; Masri R; Umi Farida; Ansar (Journal of Indonesian Scholars for Social Research, 2023)
Abstract The issue of leadership quality is a complex and multifaceted topic. Leaders who lack a clear vision are less likely to direct their team or organization effectively. With specific goals, formulating strategies or inspiring others becomes easier. This study aimed to determine and analyze the impact of leadership quality on service in Central Mamuju Regency, focusing on career development and the motivation of public service employees. Employing a survey design and a quantitative approach, the research involved 124 employees as respondents. These respondents were selected using a simple random sampling technique, with the Slovin formula applied to refine the sample size. For data analysis, path analysis was utilized. The results indicated that in Central Mamuju Regency, the most effective way to enhance the quality of service is by focusing on employee career development. Employees who receive attention and appreciation from their leaders are more capable of delivering better service quality compared to the impacts of leadership quality and public service motivation. However, these variables also play a significant role in improving employee service quality. Career development motivates employees to be more creative, improve their abilities, and receive recognition, facilitating a better career path at work.